FSKTM E-Conference System - Rahmat, Noorshazwanie Ilya; Mahdin, Hairulnizam (Applied Information Technology And Computer Science, 2024)
This project aims to develop a tailored e-conference submission system, "FSKTM ECS," for the Faculty of Computer Science and Information Technology (FSKTM) at Universiti Tun Hussein Onn Malaysia (UTHM). Unlike existing systems like EasyChair and EDAS, FSKTM ECS addresses the specific and stringent requirements set by journals, such as JOIV, which mandates a maximum of four sections in articles and strict limitations on references. These constraints present significant challenges, necessitating a flexible and adaptable solution. The FSKTM ECS is designed to simplify article submission, ensure compliance with diverse journal guidelines, and enhance the transparency of the review process. Developed using PHP in Visual Studio Code, the system empowers faculty members to define submission requirements, aligning with evolving academic standards. By streamlining the submission and publication process, FSKTM ECS aims to foster educational excellence and facilitate the dissemination of research within FSKTM. The prototype will be developed using a prototype methodology, ensuring continuous improvement and alignment with user needs.